2022
DOI: 10.1002/wnan.1805
|View full text |Cite
|
Sign up to set email alerts
|

Interfacially responsive electron transfer and matter conversion by polydopamine‐mediated nanoplatforms for advancing disease theranostics

Abstract: Polydopamine (PDA) is an artificial melanin polymer that has been spotlighted due to its extraordinary optoelectronic characteristics and advance theranosctic applications in biomaterial fields. Moreover, interactions on the nano–bio interface interplay whereby substances exchange in response to endogenous or exogenous stimuli, and electron transfer driven by light, energy‐level transitions, or electric field greatly affect the functional performance of PDA‐modified nanoparticles. The full utilization of poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 116 publications
(185 reference statements)
0
3
0
Order By: Relevance
“…Not only critical for precise disease diagnosis, but spatiotemporal controlled-miRNA detection (one of the most typical biosensing strategies with distance constraint effects) also hold enormous potential for imaging-guided tumor treatments, calling for the novel design of multistimuli responsive nanomaterials. [195] Lately, Wang et al designed a nucleic acids-modulated nanotheranostic device for remote-controlled imaging-guided therapy based on energy coupling and transfer. [131] This multifunctional nanodevice, strictly cogated by exo/endogenous stimulations (NIR light and target miRNA), was composed of MDPA nanoparticles as nanotransducer combining fluorescence quenching ability and photothermal conversion loaded with thermal-sensitive DNA probes for target miRNA detection.…”
Section: Biomarker Imaging In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Not only critical for precise disease diagnosis, but spatiotemporal controlled-miRNA detection (one of the most typical biosensing strategies with distance constraint effects) also hold enormous potential for imaging-guided tumor treatments, calling for the novel design of multistimuli responsive nanomaterials. [195] Lately, Wang et al designed a nucleic acids-modulated nanotheranostic device for remote-controlled imaging-guided therapy based on energy coupling and transfer. [131] This multifunctional nanodevice, strictly cogated by exo/endogenous stimulations (NIR light and target miRNA), was composed of MDPA nanoparticles as nanotransducer combining fluorescence quenching ability and photothermal conversion loaded with thermal-sensitive DNA probes for target miRNA detection.…”
Section: Biomarker Imaging In Vivomentioning
confidence: 99%
“…Not only critical for precise disease diagnosis, but spatiotemporal controlled‐miRNA detection (one of the most typical biosensing strategies with distance constraint effects) also hold enormous potential for imaging‐guided tumor treatments, calling for the novel design of multistimuli responsive nanomaterials. [ 195 ] Lately, Wang et al. designed a nucleic acids‐modulated nanotheranostic device for remote‐controlled imaging‐guided therapy based on energy coupling and transfer.…”
Section: Biomarker Sensing By Responsive Change Of Distance Constrain...mentioning
confidence: 99%
“…It is known that metal–organic frameworks (MOFs) are mesoporous with high specific surface areas. , Thus, utilizing MOFs as the temples to synthesize bimetallic oxide-based nanozymes should be convenient to give countless active sites, , thus showing high enzyme-like catalytic activities against different sorts of ROS (•O 2 – , H 2 O 2 , and •OH). More attractively, recent studies revealed that o -quinone, an electron acceptor, and catechol, an electron donator, in polydopamine (PDA) could constantly transform to realize proton-coupled electron transfer, thus making electron separation and transfer in redox reaction more efficient. Besides, PDA is also a frequently used modifier in biomedicine due to its excellent biocompatibility, multiple biofunction, and simple preparation …”
Section: Introductionmentioning
confidence: 99%